Carrier-free prodrug nanoparticles based on dasatinib and cisplatin for efficient antitumor in vivo - Lu Yang; Jiaxi Xu; Zheng Xie; Faquan Song; Xin Wang; Rupei Tang (Elsevier, 2021)
Carrier-free drug self-delivery systems consisting of amphiphilic drug-drug conjugate (ADDC) with well-defined structure and nanoscale features have drawn much attention in tumor drug delivery. Herein, we report a simple and effective strategy to prepare ADDC using derivatives of cisplatin (CP) and dasatinib (DAS), which further self-assembled to form reduction-responsive nanoparticles (CP-DDA NPs). DAS was modified with succinic anhydride and then connected with CP derivative by ester bonds. The size, micromorphology and in vitro drug release of CP-DDA NPs were characterized. The biocompatibility and bioactivity of these carrier-free nanoparticles were then investigated by HepG2 cells and H22-tumor bearing mice. In vitro and in vivo experiments proved that CP-DDA NPs had excellent anti-tumor activity and significantly reduced toxicities. This study provides a new strategy to design the carrier-free nanomedicine composed of CP and DAS for synergistic tumor treatment.